El aula invertida e innovación educativa - Imbaquingo Cachipuendo, Mónica Andrea (2023)
Flipped Classroom (inverted classroom) is a pedagogical approach in which direct instruction moves from the collective learning space to the individual learning space and is presented as a valuable available technique, in the face of the increasing use of virtual media for learning, relying on new paradigms, which require teaching commitment. In this sense, the objective of this research is to analyze the incidence of the flipped classroom and educational innovation in the teaching-learning process of the fifth grade of Basic Middle Education of the "Belisario Quevedo" Educational Unit. The applied methodology is mixed research, since it allows interpreting, graphing and analyzing results, explaining relevant aspects focused on the flipped classroom and educational innovation, the method used is deductive-inductive, along with the types of bibliographic, documentary and research field. For the collection of information, the interview technique and a survey for the compilation of data were used, being applied to 36 students, 35 parents and a teacher of the institution, obtaining data that was analyzed and interpreted to determine the problem of study. In this way, the results obtained revealed that traditionalist pedagogical models still prevail, in addition to the lack of training for teachers on the importance and implementation of the flipped classroom as a methodological strategy. For this reason, it is concluded that in the educational establishment it is used in a basic way, technological resources and the inverted classroom in the teaching-learning process.